WISDOM-BASED THINKING FOR UNIVERSITY STUDENTS - Hayder Al-Musawi, Prof. Dr. AbdulAziz Hayder Al-Musawi (IJRDO - Journal of Social Science and Humanities Research, 2016)
The study aims to identify the wisdom- based thinking for the students of Al-Qadisiyh University in Iraq. The scale of wisdom – based thinking has been built consisted of 36 items. As a result, the university students have this type of thinking and it is influenced by the sex of the students and the class.